(untitled) (Discourse of Law and Administration, 2023)
Certain tax-law institutions comprise the authority to act within the scope of discretionary power. The extent of such discretion on the part of administrative authorities is limited by the notion of boundaries of discretion. Such boundaries lack a legal definition. Their grounds and nature are subject to discovery by the jurisprudence and administrative courts’ case law. Attention is drawn in the present paper specifically to the constitutional principles, rules of tax procedure and directives for selection of legal consequences.